2011
DOI: 10.1016/j.ejso.2011.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Type IV collagen as a tumour marker for colorectal liver metastases

Abstract: Type IV collagen has the potential to be used as tumour associated biomarker for CLM. These results indicate the importance of interaction between cancer cells and the stroma in the tumour microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 29 publications
4
41
1
Order By: Relevance
“…This finding was unexpected as other studies had shown increased progression and poor survival in cases with high type IV collagen tissue expression (16,17,30). Our data were the result of a blinded evaluation of the type IV collagen expression.…”
Section: Nonmalignant Epithelium Invasive Frontcontrasting
confidence: 48%
See 3 more Smart Citations
“…This finding was unexpected as other studies had shown increased progression and poor survival in cases with high type IV collagen tissue expression (16,17,30). Our data were the result of a blinded evaluation of the type IV collagen expression.…”
Section: Nonmalignant Epithelium Invasive Frontcontrasting
confidence: 48%
“…Indeed, type IV collagen has been found to correlate to disease activity as removal of colorectal liver metastases lead to a decrease in the serum type IV collagen concentration. In addition, recurrence of disease was associated with an increase in the type IV collagen concentration (16).…”
Section: Nonmalignant Epithelium Invasive Frontmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated levels of circulating fragments of collagen type I, III and IV have been associated with different cancer types, including head and neck cancer [17], breast cancer [18,19], liver cancer [20], colorectal liver metastases [21] and for the hepatic failure following liver resection for hepatocellular carcinoma [22]. This indicates that collagen degradation and release of fragments to the circulation is an ongoing event in many types of cancer, and that collagen degradation markers may be applicable to disease monitoring in several cancer types.…”
Section: Discussionmentioning
confidence: 99%